Inscuteable Regulates the Pins-Mud Spindle Orientation Pathway - Mauser, Jonathon F. (Public Library of Science, 2012)
During asymmetric cell division, alignment of the mitotic spindle with the cell polarity axis ensures that the cleavage furrow separates fate determinants into distinct daughter cells. The protein Inscuteable (Insc) is thought to link cell polarity and spindle positioning in diverse systems by binding the polarity protein Bazooka (Baz; aka Par-3) and the spindle orienting protein Partner of Inscuteable (Pins; mPins or LGN in mammals). Here we investigate the mechanism of spindle orientation by the Insc-Pins complex. Previously, we defined two Pins spindle orientation pathways: a complex with Mushroom body defect (Mud; NuMA in mammals) is required for full activity, whereas binding to Discs large (Dlg) is sufficient for partial activity. In the current study, we have examined the role of Inscuteable in mediating downstream Pins-mediated spindle orientation pathways. We find that the Insc-Pins complex requires Gαi for partial activity and that the complex specifically recruits Dlg but not Mud. In vitro competition experiments revealed that Insc and Mud compete for binding to the Pins TPR motifs, while Dlg can form a ternary complex with Insc-Pins. Our results suggest that Insc does not passively couple polarity and spindle orientation but preferentially inhibits the Mud pathway, while allowing the Dlg pathway to remain active. Insc-regulated complex assembly may ensure that the spindle is attached to the cortex (via Dlg) before activation of spindle pulling forces by Dynein/Dynactin (via Mud).